Analysis of Minimally Invasive Left Thoracotomy HVAD Implantation – A Single-Center Experience - Reichart, D.; Brand, C.F.; Bernhardt, A.M.; Schmidt, S.; Schaefer, A.; Blankenberg, S.; Reichenspurner, H.; Wagner, F.M.; Deuse, T.; Barten, M.J. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Minimally invasive left ventricular assist device (LVAD) implantation may reduce peri-/postoperative complications and risks associated with resternotomies. In this study, we describe our first results using a minimally invasive LVAD implantation technique (lateral thoracotomy [LT] group). These results were compared with LVAD implantations done via full median sternotomy (STX group).Methods HVAD (HeartWare, Framingham, Massachusetts, United States) implantations in 70 patients (LT group n = 22, 52 ± 15 years old; STX group n = 48, 59 ± 11 years old) were retrospectively analyzed. Minimally invasive access via left thoracotomy was feasible in 22 patients. Peri- and postoperative analyses of survival and adverse events were performed.Results No survival differences were observed between the LT and STX group (p = 0.43). LT patients without temporary right ventricular assist device (tRVAD) showed a significantly better survival rate compared to LT patients with concomitant tRVAD implantation (p = 0.02), which could not be demonstrated in the STX group (p = 0.11). Two LT and four STX patients were successfully bridged to heart transplantation and three STX patients were successfully weaned with subsequent LVAD explantations. LVAD-related infections (n = 4 LT group vs n = 20 STX group, p = 0.04) were less likely in the LT group. No wound dehiscence occurred in the LT group, whereas five were observed in the STX group (p = 0.17). The amount of perioperative blood transfusions (within the first 7 postoperative days) did not differ in both study groups (p = 0.48).Conclusion The minimally invasive approach is a viable alternative with the possibility to reduce complications and should be particularly considered for bridge-to-transplant patients.
Keywords: heart failure; left ventricular assist device implantation; minimally invasive; thoracotomy; sternotomy